MEANING ANALYSIS OF MOUNTAIN AND HILL NAMES IN TASIKMALAYA - Resti Febrisanti; Anggi Andini; Dwi Anggi C; Dinda Nurdiana; Aveny Septi Astriani (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to know and explain the meaning of the names of mountains and hills in Tasikmalaya, namely Mount Galunggung, Mount Bongkok, Mount Payung, Bukit Panyangrayan, and Bukit Pandawa. This method uses qualitative descriptive methods with data collection techniques. Based on the results of the study, meanings were found in the names of mountains and hills derived from the shape, location, and historical connection. It can be concluded that the meaning of the names of mountains and hills in Tasikmalaya comes from the shape, location, and connection with the history of the formation of the names of mountains and hills.